2021
DOI: 10.3389/fpsyg.2021.572437
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Cognitive Load Using In-Game Metrics of a Serious Simulation Game

Abstract: Serious games have become an important tool to train individuals in a range of different skills. Importantly, serious games or gamified scenarios allow for simulating realistic time-critical situations to train and also assess individual performance. In this context, determining the user’s cognitive load during (game-based) training seems crucial for predicting performance and potential adaptation of the training environment to improve training effectiveness. Therefore, it is important to identify in-game metr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 82 publications
0
16
0
4
Order By: Relevance
“…The contrasting results of the mentioned studies point out that it is important to decrease cognitive load level whereas increase learning performance of students in gamified activities (Shaban et al, 2021). Regardless of the reason of cognitive load, it should be applied the learning activities by considering the critical importance to manage it (Ayres, 2020;Sevcenko et al, 2021).…”
Section: Cognitive Load In Gamified Coursementioning
confidence: 98%
See 2 more Smart Citations
“…The contrasting results of the mentioned studies point out that it is important to decrease cognitive load level whereas increase learning performance of students in gamified activities (Shaban et al, 2021). Regardless of the reason of cognitive load, it should be applied the learning activities by considering the critical importance to manage it (Ayres, 2020;Sevcenko et al, 2021).…”
Section: Cognitive Load In Gamified Coursementioning
confidence: 98%
“…However, Turan et al (2016) determined that students had highly cognitive load level in gamification process. Sevcenko et al (2021) reported that cognitive load depended on not only the complexity of the activity but also timing of the task as it might quickly change when performing the task. They also stressed that even if each student was performing the same task, they might make different mental effort.…”
Section: Cognitive Load In Gamified Coursementioning
confidence: 99%
See 1 more Smart Citation
“…The game information module contains game information such as game goals, game rules (steps), and points. This module is designed to reduce the cognitive load on students' memory for understanding complex game rules (Sevcenko et al, 2021). The game information module also includes a real-time display of students' current points, so that students can self-review their learning performance and reflect on their points (Kim & Castelli, 2021).…”
Section: Student Modulementioning
confidence: 99%
“…Each game element and task content have an impact on students' cognitive load. Overly complicated rules or learning content can cause too much cognitive load for students to enjoy the activity or game and can thus prevent them from learning (Sevcenko et al, 2021). In addition, students' prior knowledge is another a factor that affects the cognitive load during game play.…”
Section: Introductionmentioning
confidence: 99%